Analysis of the current status and influencing factors of nurses’ patient safety competence: a potential profile analysis - Xiao, Qian; Huang, Xi; Ren, Xin; Wen, Xiulin; Zhao, Yujian (Frontiers in Medicine, 2024)
To understand the current situation of patient safety competence level of hospital nurses, identify potential categories, and analyze the distribution characteristics of demographic variables in each subgroup. Methods: A total of 1996 nursing staff were selected as the research objects by convenience sampling method, and the questionnaire survey was conducted using the Chinese version of the Patient Safety Ability Scale, and the three dimensions of the Patient Safety Ability Rating Scale were used as explicit variables for potential profile analysis, and the influencing factors of different potential profiles of nurses' patient safety ability were analyzed by logistic regression.The safety ability of 1996 nurses could be divided into three potential categories: "ability risk group" (14.3%), "medium ability group" (32.9%) and "ability advantage group" (52.7%), with monthly income, participation in department training, self-learning and love of nursing as the influencing factors.The overall patient safety ability of nurses is at the upper middle level, and the classification of nurses can be predicted by monthly income, participation in department training, self-directed learning and love of nursing, and nursing managers can formulate targeted interventions according to the influencing factors of potential profiles to improve nurses' patient safety ability.